Differential time responses in inflammatory and oxidative stress markers after a marathon: An observational study - List Larsen, E.; Enghusen Poulsen, H.; Michaelsen, C.; Kofoed Kjær, L.; Lyngbæk, M.; Skytte Andersen, E.; Petersen-Bønding, C.; Lemoine, C.; Gillum, M.; Rye Jørgensen, N.; Ploug, T.; Vilsbøll, T.; et al. (Journal of Sports Sciences, 2020)
Acute and adaptive changes in systemic markers of oxidatively generated nucleic acid modifications (i.e., 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG) and 8-oxo-7,8-dihydroguanosine (8-oxoGuo)) as well as inflammatory cytokines (i.e., C-reactive protein, interleukin-6, interleukin-10, and tumour necrosis factor alpha), a liver hormone (i.e., fibroblast growth factor 21 (FGF21)), and bone metabolism markers (sclerostin, osteocalcin, C-terminal telopeptide, and N-terminal propeptide of type 1 procollagen) were investigated following a marathon in 20 study participants. Immediate changes were observed in inflammatory cytokines, FGF21, and bone metabolism markers following the marathon. In contrast, no immediate changes in urinary excretion of 8-oxodG and 8-oxoGuo were evident. Four days after the marathon, decreased urinary excretion of 8-oxodG (-2.9 (95% CI -4.8;-1.1) nmol/24 h, P < 0.01) and 8-oxoGuo (-5.8 (95% CI -10.3;-1.3) nmol/24 h, P = 0.02) was observed. The excretion rate of 8-oxodG remained decreased 7 days after the marathon compared to baseline (-2.3 (95%CI -4.3;-0.4) nmol/24 h, P = 0.02), whereas the excretion rate of 8-oxoGuo was normalized. In conclusion marathon participation immediately induced a considerable inflammatory response, but did not increase excretion rates of oxidatively generated nucleic acid modifications. In fact, a delayed decrease in oxidatively generated nucleic acid modifications was observed suggesting adaptive antioxidative effects following exercise.